3D x-ray microtomography investigations on the bimodal porosity and high sulfur impregnation in 3D carbon foam for Li–S battery application. (1st January 2022) - Thripuranthaka, M; Chaturvedi, Vikash; Dwivedi, Pravin Kumari; Torris, Arun; Shelke, Manjusha V
Abstract: Lithium–sulfur (Li–S) batteries, regarded as one of the most promising alternatives to current state-of-the-art rechargeable Li-ion battery technologies, have received tremendous attention as potential candidates for next-generation portable electronics and the rapidly advancing electric vehicle market. However, substantial capacity decay, miserable cycle life, and meagre stability remain critical challenges. More specifically, shuttling of polysulfide (Li2 S x (3 < x ⩽ 8)) species severely hinders the cycle performance resulting in capacity fade and cycling instability. In the present work, a highly conducting three-dimensional (3D) carbon nanofiber (CNF) foam has been synthesized using the lyophilization method followed by thermal pyrolysis. The highly porous foam materials have a bimodal porosity distribution in the nano and micro regime and were successfully investigated to serve as a potential host for sulfur species intended for Li–S battery application. 3D x-ray microtomography was employed to estimate the nature of sulfur impregnation and distribution in the 3D porous networks. On utilizing the final product as cathode material, sulfur impregnated carbonized CNF foam and modified the separator with functionalized multiwalled carbon nanotubes delivered a specific capacity of ∼845 mAh g −1 at 100 mA g −1 .